Relationship between health literacy of cancer patients and shared clinical decision-making in a Middle East country (Epidemiology, Biostatistics, and Public Health, 2022)
Introduction: The study aimed to investigate the relationship between Health literacy (HL) and shared clinical decision-making among cancer patients in Iran.Methods: A cross-sectional questionnaire survey was performed in the south of Iran between January and March of 2017. The study's population was all patients in the southeast of Iran. From here, 500 patients were selected as the study sample by the stratified sampling method. Two standard questionnaires were selected for data-gathering. The data was analyzed using SPSS version 21.0.Results: About 52% of patients did not have enough HL and 47% had a poor participation record in clinical decision-making. There is a positive statistical relationship between HL and participation in clinical decision-making among cancer patients (P=0.001). About 49% of the patients with low HL had poor participation in clinical decision-making. Moreover, HL had a relationship with age, gender, education, place of living, region, and type of cancer (P>0.05).Conclusion: HL among cancer patients is limited and has a positive impact on decision-making in clinical participation. Physicians must try and boost HL among patients. Higher HL helps patients engage in their clinical decision-making. Health workers are an important source for increasing HL among patients.